A discrete choice experiment to estimate public willingness to pay for attributes of water services in Terengganu, Malaysia - Nur Syuhada Che Ibrahim; Mahirah Kamaludin; Nur Fatihah Shaari (Penerbit Universiti Kebangsaan Malaysia, 2019)
Water service is usually taken for granted as important amenities with required levels needed, however little is known about how much consumers are willing to pay for particular water service levels. Improved water services should be based on the understanding built upon consumers’ choice and preferences. Thus, this study aims to estimate willingness to pay (WTP) of consumers in Terengganu, Malaysia for improvement in domestic water services. A choice experiment method was conducted to assess consumer preferences for water service attributes: i.e. water quality, water disruption, water pressure and water price. Primary data were collected using face-to-face interviews of structured questionnaire from a sample of residents in eight districts in Terengganu. A conditional logit model was carried out for data regression. The results showed significant willingness to pay (WTP) and the contribution of the level of education, age and income in supporting the specific attributes of water services improvements. Identifying the attributes and their prices based on consumers’ preferences would help water provider to recognize and deliver preferred water service attributes, effective water tariff policy for cost recovery and water service sustainability to consumers.